1988
DOI: 10.1590/s0373-55241988000100006
|View full text |Cite
|
Sign up to set email alerts
|

Bioecologia de crustáceos decápodos, braquiúros, no sistema baía-estuário de Santos e São Vicente, SP: 1. Ocorrência e composição

Abstract: De junho de 1985 a maio de 1936, foi realizado um programa de pesquisa no complexo baia-estuário de Santos e São Vicente, SP. Para a obtenção do material foram utilizadas redes de arrasto de fundo, e de praia, além de armadilhas. As operações de pesca capturaram 14 espécies de decápodos brachiuros, por meio de arrastos de fundo; oito com os arrastos de praia; e cinco, no estuário, utilizando armadilhas iscadas, sendo, estas ultimas, todas pertencentes ao gênero Callinectes. Callinectes danae dominou nos três a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
(3 reference statements)
1
7
0
2
Order By: Relevance
“…Despite the wide distribution of C. danae along the Brazilian Atlantic coast, from Paraíba to Rio Grande do Sul (Melo et al, 1989), on its ecology is from in the Mundaú Lagoon, Alagoas State (Pereira- Barros & Travassos, 1975), in Santos Bay, São Paulo State (Pita et al, 1985;Moreira et al, 1988), and reproductive cycle in the Ubatuba region (Costa & Negreiros-Fransozo, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the wide distribution of C. danae along the Brazilian Atlantic coast, from Paraíba to Rio Grande do Sul (Melo et al, 1989), on its ecology is from in the Mundaú Lagoon, Alagoas State (Pereira- Barros & Travassos, 1975), in Santos Bay, São Paulo State (Pita et al, 1985;Moreira et al, 1988), and reproductive cycle in the Ubatuba region (Costa & Negreiros-Fransozo, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Portunus spinimanus and Callinectes larvatus were recorded in low frequencies by Pita et al (1985b): only 1 specimen of C. larvatus and 15 of Portunus spinimanus. Similarly, Moreira et al (1988) caught P. spinimanus in areas along the beaches and in the bay, always with low occurrence frequencies. For an eight-year period, Severino- Rodriguez et al (2001) observed the landings of the local crab fishery, and mentioned neither species.…”
Section: Resultsmentioning
confidence: 93%
“…Three additional species, Persephona punctata (Linnaeus, 1758), P. mediterranea (Herbst, 1794) and Menippe nodifrons Stimpson, 1859 were found by Moreira et al (1988). Similarly to Pita et al (1985b), these investigators used different collection methods which increased the sampling area, and along the rocky shore they caught specimens of the Guaiá crab, M. nodifrons, which normally occurs in these habitats (Oshiro 1999).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations